Surveillance and outbreak response of hand - foot - mouth disease in Haiphong Children's Hospital, Vietnam - Sang Ngoc Nguyen; Chuc Van Dang; Tham Thi Tran (Taylor & Francis Group, 2021)
Hand, foot, and mouth disease (HFMD) is a public health issue in Haiphong, as it is in Vietnam overall. In 2011, a large outbreak of HFMD in Vietnam resulted in 113,121 children seeking medical attention, of whom 170 died. According to a Vietnam General Department of Preventive Medicine report in 2012, HFMD has the 2nd highest incidence of pediatric disease among 10 common diseases. There were 157,654 cases, of which 45 patients died, ranking 3rd among Vietnamese children's causes of death. In 2017, HFMD broke out again in Haiphong. Haiphong Children's Hospital (HCH) is the only hospital in Haiphong to examine and treat HFMD for children. This study aims to describe the clinical characteristics of HFMD seen in HCH and review the results of disease control efforts in 2017. A retrospective descriptive study. Clinical data were obtained by reviewing the patients' case records from January 2017 through December 2017 in HCH. There were 2610 patients admitted to HCH in 2017. Most patients were under 3 years old (94.8%). The disease prevalence increased from April 1st through September 30th. Common symptoms were: fever (99%), mouth ulcers, sore throat (96.4%), rash on hand and foot (64.4%), startle (33.9%). Diagnosis mainly was clinical-grade 2a (79.8%). PCR was performed in 526 patients with grade 2b, 3, 4, and 218 cases (41.4%) were positive with EV71. Most of the cases' prognosis was excellent, with 99.3% of cases cured and no deaths. Despite stringent measures taken in kindergartens, it is clear that HFMD is currently a public health problem in Vietnam. It is a highly contagious infectious disease, including several potential complications, and results in a number of cases leading to death. The disease is a particular cause of concern, especially when HFMD cases can overload already crowded hospitals. A high degree of vigilance should be maintained over the disease and its consequences.